Temperatura powietrza i wielkość opadów atmosferycznych w województwie łódzkim w latach 1966-2021 - Balcerzak, Patrycja; Kolendowicz, Leszek; Półrolniczak, Marek (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The aim of the study is to investigate the course of air temperature and precipitation in Łódź Province in 1966–2021. The study uses daily data provided by the IMGW-PIB net from three meteorological stations: Łódź–Lublinek, Sulejów, and Wieluń. The average air temperature in Łódź province is 8.3ºC. When analyzing the annual course of air temperature, the lowest values were recorded in January (2.1ºC on average), the highest were recorded in July (18.4ºC). A growing, statistically significant trend in air temperature was observed at all the stations in the analyzed multi-year period. The rate of changes in the average air temperature in Łódź province reached the maximum value of 0.35°C/10 years at all the three analyzed stations. The average rainfall totals in Łódź province are not very diversified. The average annual sum of precipitation in the analyzed period in Łódź province ranged from 562.2 mm to 597.2 mm. On a seasonal scale, the heaviest precipitation was in the summer months (June–August), and the lowest in winter (December–February), while autumn rainfallwas slightly higher than in the spring. The biggest amounts of rainfall were recorded in July (84.8 mm), while the minimum rainfall was in February (25.8 mm). At all the stations, there was an upward trend in precipitation in the spring and autumn, and a downward trend in the summer. On average, in Łódź province there were 169 days with precipitation.